81.9k views
3 votes
Question 20 of 32

If f(x) = 4x2 - 6 and g(x) = x2 - 4x - 8, find (f - g)(x).
O A. (f- g)(x) = 5x2 - 4x - 14
O B. (f - g)(x) = 3x2 - 4x - 2
O c. (f- g)(x) = – x2 - 14
O D. (f- g)(x) = 3x2 + 4x + 2
SUBMIT

User Shardul
by
5.0k points

1 Answer

4 votes

(f - g)(x) = f(x) - g(x)

(f - g)(x) = ( f(x) ) - ( g(x) )

(f - g)(x) = (4x^2 - 6) - ( x^2 - 4x - 8)

(f - g)(x) = 4x^2 - 6 - x^2 + 4x + 8

(f - g)(x) = (4x^2-x^2) + 4x + (-6+8)

(f - g)(x) = 3x^2 + 4x + 2

Answer: Choice D

User Farooq
by
5.0k points